HERMENEUTIKA EMILIO BETTI: ANALISISNYA ATAS KISAH AṢḤĀB AL-FĪL DALAM TAFSĪR AL-MUNĪR - Muhammad Zulfikar Nur Falah (Sekolah Tinggi Agama Islam Sadra, 2022)
This article analyzes the story of aṣḥāb al-fīl in Tafsīr Al-Munīr with Emilio Betti's hermeneutics. Meanwhile, in essence, the Al-Qur'an itself contains various kinds of miracles which contain various unseen information and of course the story of the past aṣḥāb al-fīl, cannot be represented and stated rationally sense. The research method in this article uses descriptive analysis obtained through library research, with relevant and reliable sources, such as books, journals, theses, dissertations, and so on. Before obtaining a detailed understanding of Emilio Betti's analysis of Tafsīr Al-Munīr, the author first describes the biography and theory of Emilio Betti's hermeneutics. This is so implicative, because it is able to produce a reflective reinterpretation to be applied critically and systematically. Based on Emilio Betti's hermeneutical analysis, the story of aṣḥāb al-fīl is interpreted by Wahbah Al-Zuhaili by giving nuances of methodological privilege and uniqueness in understanding the meaning contained in the Al-Qur'an. Because it requires an objective interpretation, in Emilio Betti's analysis, Al-Zuhaili quite meets the requirements of his hermeneutic theory, both looking at his linguistic phenomena, emptying himself of any interest, even penetrating the dimensions of reconstruction by including situations and conditions, in addition to both revealing and showing as an interpreter existential in search of meaning, must be aligned with the intent of the author of the text itself.